The Determinants of Earnings: A Behavioral Approach - Bowles, Samuel; Gintis, Herbert; Osborne, Melissa (Journal of Economic Literature, 2001)
We survey the determinants of earnings and propose a framework for understanding labor market success. We suggest that the advantages of the children of successful parents go considerably beyond the benefits of superior education, the inheritance of wealth, or the genetic inheritance of cognitive ability. We suggest that noncognitive personality variables, such as attitudes towards risk, ability to adapt to new economic conditions, hard work, and the rate of time preference affect both earning and the transmission of economic status across generations.